Ambipolar Resistive Switching in an Ultrathin Surface-Supported Metal-Organic Framework Vertical Heterojunction - Albano, Luiz G. S.; Vello, Tatiana P.; Camargo, Davi H. S. de [UNESP]; Silva, Ricardo M. L. da [UNESP]; Padilha, Antonio C. M.; Fazzio, Adalberto; Bufon, Carlos C. B. [UNESP] (Amer Chemical Soc, 2020)
Memristors (MRs) are considered promising devices with the enormous potential to replace complementary metal-oxide-semiconductor (CMOS) technology, which approaches the scale limit. Efforts to fabricate MRs-based hybrid materials may result in suitable operating parameters coupled to high mechanical flexibility and low cost. Metal-organic frameworks (MOFs) arise as a favorable candidate to cover such demands. The step-by-step growth of MOFs structures on functionalized surfaces, called surface-supported metal-organic frameworks (SURMOFs), opens the possibility for designing new applications in strategic fields such as electronics, optoelectronics, and energy harvesting. However, considering the MRs architecture, the typical high porosity of these hybrid materials may lead to short-circuited devices easily. In this sense, here, it is reported for the first time the integration of SURMOF films in rolled-up scalable-functional devices. A freestanding metallic nanomembrane provides a robust and self-adjusted top mechanical contact on the SURMOF layer. The electrical characterization reveals an ambipolar resistive switching mediated by the humidity level with low-power consumption. The electronic properties are investigated with density functional theory (DFT) calculations. Furthermore, the device concept is versatile, compatible with the current parallelism demands of integration, and transcends the challenge in contacting SURMOF films for scalable-functional devices.
Keywords: Metal-organic frameworks (MOFs); HKUST-1; resistive switching; scalable-functional devices; strained nanomembranes